The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1155/2020/2928945
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Nomogram of Transfusion and Associated Complications in Nonfracture Patients following Total Hip Arthroplasty

Abstract: The incidence, risk factors, and associated complications of perioperative transfusion in nonfracture patients following total hip arthroplasty (THA) are unclear. The aim of the present research was to study the predictors of transfusion risk in nonfracture patients following THA and develop a nomogram. One thousand six hundred and thirty-five patients who underwent THA due to nonfracture disease in our institution between September 2013 and July 2017 were included. Independent predictors of transfusion were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Moreover, our predictive model aims for all adult patients following orthopaedic surgeries. This was different from other studies that targeted patients with particular conditions, for instance, Peng et al 18 formulate a nomogram for elderly patients with hip fracture, and Wang et al 19 establish a model for nonfracture patients following total hip arthroplasty. From this point of view, our predictive model has wider clinical applicability than others.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, our predictive model aims for all adult patients following orthopaedic surgeries. This was different from other studies that targeted patients with particular conditions, for instance, Peng et al 18 formulate a nomogram for elderly patients with hip fracture, and Wang et al 19 establish a model for nonfracture patients following total hip arthroplasty. From this point of view, our predictive model has wider clinical applicability than others.…”
Section: Discussionmentioning
confidence: 77%
“…Perioperative blood management is essential in preventing these complications. Gilbody et al reported the incidence of postoperative blood transfusion after THA to be between 16.9% and 50%, with about half of postoperative blood transfusions exceeding 2 units [ 3 , 10 ]. However, transfusion can lead to transfusion-related complications, increase the risk of bacterial infection and death, and may also increase economic burden [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%